Computational determination the reactivity of salbutamol and propranolol drugs - Omar, Rebaz A.; Koparir, Pelin; Ahmed, Lana O.; Koparir, Matin (DergiPark, 2020)
Gaussian software programs 09 was utilized to find the reactivity of salbutamol (SAL) and propranolol (PRO). Density Functional Theory (DFT) and Hartree-Fock (HF) were used to determine the energy band gaps. B3LYP/6-31++G(d,p) lower energy level was chosen as the base set. Geometrical structures with frontier molecular orbitals estimation for both the SAL and PRO. Atomic charge distribution and molecular electrostatic potential evaluation were performed for both drugs. For thermodynamic analysis Ab-initio DFT with HF at 6-31++G base sets were accomplished. The results showed that the PRO is more reactive than SAL. © 2020. All Rights Reserved.
Keywords: Density Functional Theory (DFT); Frontier molecular orbitals; Hartree-Fock (HF); Propranolol (PRO); Salbutamol (SAL)